Design of Control System for Lower Limb Rehabilitation Robot based on Pole Placement Algorithm - Sun, Li (IEEE Information Technology, Networking, Electronic and Automation Control Conference (Online), 2021)
Aiming at the problem that control systems of current lower limb rehabilitation robot complicated parameter settings and inclusion of rehabilitation training of the ankle joint,a control system for a lower limb rehabilitation robot based on pole placement algorithm is proposed.According to the nonlinear motion of themechanical structures for lower limb joints,the pole assignment algorithm is used to design the controller.The controller is discretized by z-transform.The closed-loop position control is realized in the STM32 microcontroller,using ARM-M3 as the kernel.STM32 microcontroller communicates with the host computer through serial port protocol.Touch screen controls microprocessor,so as to control the movement of the lower limb rehabilitation robot.And transmitts the angle signal and force signal of each joint to the host computer for curve display in real time.The passive walking training of 8 subjects under different weight support ratios is tested.By analyzing the joint angle curve and joint driving force curve,the control system realizes the coordinated and stable control of lower limb rehabilitation robot under different rehabilitation training modes.It is concluded that the lower limb rehabilitation robot with the developed controllers meet certain rehabilitation training requirements.